Comparative Effectiveness Of Treatment Of Oral Hemangiomas With Ir-Lasers - Karimov M.A; Sadikov R.R; Makhmudova R.Y; Yakubov A.A; Turgunov Z; Rachimberdieva G.A (Genius Publishing Group, 2023)
This article describes the clinical, dissemination, modern diagnosis, stages of development, classification and modern treatments of hemangioma, as well as the results of treatment with IR-lasers, as well as medicamentous treatment, sclerotic treatment and joint treatment. The study analyzed the results of the treatment of 178 patients.
Keywords: Hemangioma; IR-laser; sclerotic treatment